2012
DOI: 10.1088/1751-8113/45/14/143001
|View full text |Cite
|
Sign up to set email alerts
|

Cold atoms in the presence of disorder

Abstract: The review deals with the physics of cold atomic gases in the presence of disorder. The emphasis is on the theoretical developments, although several experiments are also briefly discussed. The review is intended to be pedagogical, explaining the basics and, for some of the topics, presenting rather detailed calculations . arXiv:1112.5736v1 [cond-mat.quant-gas]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 110 publications
(436 reference statements)
3
132
0
Order By: Relevance
“…Needless to say, these strengths largely exceed those observed in typical optical lattice experiments, which conversely makes cold atoms loaded into optical lattices a system of choice to attain URL and CPA regimes. In fact, if disorder is not purposely introduced, e.g., via an additional speckle potential [58,68], the optical lattice periodicity is practically ideal, as only randomness in the number of cold atoms loaded into each well is, in general, present. To this purpose, we have also ascertained the effect of random fluctuations δN j in the atomic density N and found that such a source of structural disorder entails changes in the reflectivities (R L and R R ) and the eigenvalues (|λ + s | and |λ − s |) that amount to a tiny fraction of percents (∼0.2%) of the changes one would observe, e.g., for disorder in the distribution width d (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Needless to say, these strengths largely exceed those observed in typical optical lattice experiments, which conversely makes cold atoms loaded into optical lattices a system of choice to attain URL and CPA regimes. In fact, if disorder is not purposely introduced, e.g., via an additional speckle potential [58,68], the optical lattice periodicity is practically ideal, as only randomness in the number of cold atoms loaded into each well is, in general, present. To this purpose, we have also ascertained the effect of random fluctuations δN j in the atomic density N and found that such a source of structural disorder entails changes in the reflectivities (R L and R R ) and the eigenvalues (|λ + s | and |λ − s |) that amount to a tiny fraction of percents (∼0.2%) of the changes one would observe, e.g., for disorder in the distribution width d (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Many important contributions have been developed in the field of condensed matter theory [2], which now -upon the emergence of ultracold atomic experiments -can be precisely analyzed and verified. However, along with the new experimental possibilities, novel theoretical concepts need to be devised which capture the whole realm of present-day technologies [75] and, more importantly, foster a fundamental understanding of multi-scale transport phenomena.…”
Section: Aim Of This Thesismentioning
confidence: 99%
“…The thus obtained random pattern of bright (constructive interference) and dark spots (destructive interference) constitutes a single static realization of a disorder potential, and can be characterized by an average grain size with transverse and longitudinal extension (in the far-field) proportional to [75]. Here, λ L , D, and z are the corresponding wavelength of the laser field, the diameter of, and the distance perpendicular to the diffusing plate.…”
Section: Atoms In Disordered Potentialsmentioning
confidence: 99%
“…Understanding the propagation of classical waves through strongly scattering media is of great importance for many applications such as imaging, characterization, or communication with all kinds of waves [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%